2019
DOI: 10.1515/jmbm-2019-0002
|View full text |Cite
|
Sign up to set email alerts
|

A note on the effect of surface topography on adhesion of hard elastic rough bodies with low surface energy

Abstract: Adhesion between bodies is strongly influenced by surface roughness. In this note, we try to clarify how the statistical properties of the contacting surfaces affect the adhesion under the assumption of long-range adhesive interactions.Specifically, we show that the adhesive interactions are influenced only by the roughness amplitude hrms, while the rms surface gradient h0rmsonly affects the non-adhesive contact force. This is a remarkable result if one takes into account the intrinsic difficulty in defining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…Moreover, Violano et al [26] studied the adhesive rough contact between self-affine fractal surfaces with an advanced multiasperity model, where adhesion is implemented according to Derjaguin, Muller & Toporov (DMT) force-approach [27]. In their simulations, the pull-off force is almost independent on the value of h ′ rms , again in agreement with most of the criteria introduced in refs.…”
Section: Introductionsupporting
confidence: 60%
“…Moreover, Violano et al [26] studied the adhesive rough contact between self-affine fractal surfaces with an advanced multiasperity model, where adhesion is implemented according to Derjaguin, Muller & Toporov (DMT) force-approach [27]. In their simulations, the pull-off force is almost independent on the value of h ′ rms , again in agreement with most of the criteria introduced in refs.…”
Section: Introductionsupporting
confidence: 60%
“…In such case, surface roughness is described by several length-scales and a greater load is required to create new contact patches on smaller wavelengths. Specifically, as shown in [34], the dependence of the curves on ζ (and thus on h rms ) is exclusively due to the contribution of the repulsive interactions.…”
Section: Adhesive Hysteresis and Pull-off Force: Effect Of The Fractal Parametersmentioning
confidence: 87%
“…In such case, a DMT-type approach, based on the assumption of long-range adhesion interactions, could be more accurate in modeling the contact problem. In this regard, a DMT-type model is developed in [34] with the aim of investigating the adhesive contact of surfaces with h rms of the order of 1 nm. It is found that F po is almost independent of h rms , i.e., the adhesion force required for the detachment is magnification independent.This is confirmed in [38], where a stickiness criterion [38] is derived from Persson-Scaraggi DMT theory [37].…”
Section: Adhesive Hysteresis and Pull-off Force: Effect Of The Fractal Parametersmentioning
confidence: 99%
“…7(d). This is typical of statistical models based on independent asperities, like ours, because they neglect interaction and coalescence of neighboring microjunctions [51,52]. To test this explanation, a boundary element method (BEM) [57] is applied to predict the real contact area under purely normal loading (i.e.…”
Section: Quantitative Comparison With Experimentsmentioning
confidence: 98%